Coal Handling At TVA's Paradise Steam Station Paradise, Kentucky ? Introduction - Stanley Kesler (Society for Mining, Metallurgy & Exploration, 1962)
The first of two initial 650-mw units of the Paradise Steam Station, located on the banks of the Green River in the south-central portion of the western Kentucky coal basin, is scheduled for operation in late fall of 1962. Location of the site is shown on the map of figure 1. This plant will be the eighth, large-capacity,, modern station built by TVA in a series starting with Johnsonville, operated first in 1951. During that period of 10 years,, unit sizes have increased from a capability of 125 mw to 500 mw at the recently completed Widows Creek Unit 7 addition and at Paradise to 650 mw. This new unit will take its place in a power system that serves an area of some 80,000; square miles with a present installed capacity of over 12,000 mw. Upon completion of the Paradise units and other additional hydro and steam units presently under construction, the system capacity will have reached over 15,000 mw. Projected load estimates indicate that this system will provide a margin' of slightly under 10 percent of dependable capacity above peak demand at that tire. One Paradise 650-mw unit at that time will represent approximately 4 percent of the total system installed capacity.